Genitalidad e (im)potencia del pensamiento: Heidegger, Deleuze, Agamben - Pimentel, Sebastián (2015)
This paper reports how according to Heidegger, Deleuze, and Agamben, both the notion of thinking and of philosophical activity, far from meaning the same, involve fundamental differences. However, our reading of the three authors also proposes to discover a common affiliation related to the contrast between “doxa” and “thinking”; Heidegger’s, Deleuze’s and Agamben’s are three ways by which we can understand the “birth” or “emergence” of thinking as an experience or activity that should not be understood as stemming from the field of communication or re-presentation. All these considerations converge finally in the subtle quality of thought as liminal “pow-er” that, according to each author, must also be understood in its paradoxical quality of “impotence”, quality much closer to the experience of in-corporation as an event (Heidegger); to the pre-supposed, non-discursive moment –and simultaneously con- stituent– of either philosophical, artistic, or scientific “creation” (Deleuze); or to the pure enjoyment of power, as the experience of a type of “deprivation”, both positive and unlimited, as well as eluding any “function” (Agamben).